DESAIN FOOD COURT DI KOTA BANJARBARU - Nafis, Muhammad; Sa'ud, Mohammad Ibnu (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Culinary is one of the attractions of the community which has experienced a lot of development to the phenomenon of hanging out culture which is currently a trend in Banjarbaru City. However, due to the absence of a place to accommodate this, a place was created in the form of a Food Court. The design of the Food Court in Banjarbaru City is the answer to this problem with the Third Place Method as a method of solving it which aims as a forum for visitors to carry out certain activities or relax while enjoying culinary delights. The concept applied is Communal Dining Place, which means a space that accommodates social activities and is used for the whole community or community. This concept is based on the actors in this design by considering the settings that are influenced by three elements, namely humans as the subject of actors, activities and human thoughts with different needs.